Mekanisme Penciptaan Uang dalam Lembaga Keuangan Syariah: Antara Prinsip Kehati-hatian dan Fungsi Intermediasi - Arnelia Putri Pratiwi; Gama Pratama; Saefullah Fatah; Alfina Damayanti; Dea Safitri; Muhammad Nurjati; Muhammad Risna Munandar; Rini Rizkiyana Ulfa; Tia Nurazizah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the mechanism of money creation in Islamic financial institutions by highlighting its relationship to the principle of prudence and the intermediation function. The research background is based on the growth of Indonesia's sharia capital market which by 2025 will reach a capitalization of IDR 5,060 trillion, but still faces conceptual challenges regarding how money is created according to the principles of maqashid al-shariah. The method used is Systematic Literature Review (SLR) with PRISMA guidance on 38 relevant scientific articles. The results of the study show that money creation in the sharia system only occurs through real asset-based economic activities, in contrast to the conventional system that relies on credit and interest expansion. The intermediation function is carried out through partnerships that prioritize proportional sharing of risk and profit, while the prudential principle ensures that monetary expansion remains under control. In addition, research has found that sharia contracts such as murabahah, mudarabah, and musharakah play a role in encouraging productive money circulation while suppressing speculative activities. This study concludes that the integration between the moral and economic dimensions forms a just, stable, and sustainable Islamic monetary paradigm. These findings make a conceptual contribution to strengthening Islamic financial policy in Indonesia, especially in formulating a monetary regulatory framework that is in line with the principles of distributive justice, transparency, and protection of the stability of the national financial system.